Thermoelectric generators for waste heat harvesting: A computational and experimental approach. (15th September 2017) - Aranguren, P.; Araiz, M.; Astrain, D.; Martínez, A.
Highlights: Thermoelectric technology used to harvest waste heat to produce electrical energy. Thermoelectric generator prototype located at the exhaust of a combustion chamber. Computational model which considers the temperature loss of the flue gases. Validated computational methodology which presents an accuracy of the ±12%. Abstract: Waste heat generation has a widespread presence into daily applications, however, due to the low-temperature grade which presents, its exploitation with the most common technologies is complicated. Thermoelectricity presents the possibility of harvesting any temperature grade heat; besides it also includes many other advantages which make thermoelectric generators perfect for generating electric power from waste heat. A prototype divided into two levels along the chimney which uses the waste heat of a combustion has been built. The experimentation has been used to determine the parameters that influence the generation and to validate a generic computational model able to predict the thermoelectric generation of any application, but specially applications where waste heat is harvested. The temperature and mass flow of the flue gases and the load resistance determine the generation, and consequently, these parameters have been included into the model, among many others. This computational model incorporates all the elements included into the generators (heat exchangers, ceramics, unions) and all the thermoelectric phenomena and moreover, it takes into account the temperature loss of the flue gases while circulating along the thermoelectric generator. The built prototype presents a 65% reduction in the generation of the two levels of the thermoelectric generator due to the temperature loss of the flue gases. The general computational model predicts the thermoelectric generation with an accuracy of the ±12%.